Visual deficiency and multi-deficiency symptoms of macro and micro nutrients element in pistachio seedling (Pistacia vera) - Afrousheh M.; Ardalan M.; Hokmabadi H. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
The effects of nitrogen, iron, magnesium, manganese and molybdenum deficiencies and multi- deficiencies on pistachio seedling (Pistacia vera) was studied in sand culture. The following treatments were employed: 1-Complete Hoagland's nutrient solution; 2-Nutrient solution lacking N; 3-Nutrient solution lacking Fe, 4-Nutrient solution lacking Mg; 5-Nutrient solution lacking Mn; 6-Nutrient solution lacking Mo; 7-distilled water; 8- Nutrient solution lacking Fe and N; 9- Nutrient solution lacking Fe and Mn; and 10- Nutrient solution lacking Fe and Mo. The experimental design used in this study was complete randomized block design with three replications. Deficiency symptoms observed were mainly leaf discoloration, necrosis, scorching, defoliation and growth stunting. Seedlings that received complete nutrient solution were healthy with dark green foliage. Reductions in height, leaf area and leaf number were noticed for various levels of deficiencies of nutrient elements. Shoot and root growth of the seedlings deficient in nutrients were also affected. Seven months after planting, shoot and root biomasses production were statistically significant at one percent level. Multi-Deficiency symptoms sound like single deficiency. Also shoot and root growth of the seedlings deficient of nutrients were affected. Visual symptoms of nitrogen- deficient seedlings also coincided with the reduction in foliar levels of the concerned element. The typical symptoms of deficiencies of various nutrient elements could be used as a guideline for diagnosing nutrient deficiencies of pistachio in commercial nurseries and plantations. The present study also showed the multi-deficiency of nutrients, new symptom appears in leaves, differs from single deficiencies. In these conditions, leaf symptoms don't agree with Minimum Law. This is a new incorporated sign that appears in leaves.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)